Diversity and distribution of dipterous flies of medical and veternary importance in Tayma, Saudi Arabia - Saud Arif Al-Enazi; Rakan Al-Enazi; Saif Al-Enazi; Turki Al-Enazi; Mamdooh Al-Enazi; Salman A. Al-Shami; Sadeq Alhag (Aceh Journal of Animal Science, 2018)
The present study aims to investigate the distribution and diversity of dipterous flies in Tayma (Saudi Arabia) during the spring of 2018. A total of 12 dipterous species were collected from three different sites located in Tayma (Tabuk, Saudi Arabia) located in the Northern part of Saudi Arabia. The taxa of flies were dominated by Musca domestica and Musca sorbens. No significant difference were observed between the total number of flies collected using different traps (t-test, P0.05) and among the studied sites (ANOVA, P0.05). The highest number of flies was recorded from Site 3 (a cattle farm). However, lower number of flies was reported from the dates palm farms. In conlusion, the species Musca domestica were found to be the most abundant species in all locations with remarkable high abundance in animal facilities (slaughter house and animal farm). The pheromone traps were found to be the most effective trap catching high number of individuls and high number of fly species.